40 Minutes with “Sang Penjemput”: A Concept of Creating Literacy Culture at SMP N 17 Kendari - Hanna, Hanna; Milwan, Milwan; Herianti, Herianti (Department Library of Governance Institut of Home Affairs, 2021)
Problem Statement: This research is conducted in response to low reading motivation of society, especially parents/guardians in spending their spare time when picking up their children after school in SMP N 17 Kendari. Purpose: This research aims to describe how “40 Minutes with Parents/Guardians (Sang Penjemput)” program has influenced reading literacy of SMP N 17 Kendari. Method: This research uses a qualitative research with library study method supported by observation. Data sources are reference books and scientific journal articles which was in line with this research. Observations are in the forms of authors’ own experiences as authors directly participated in this program. Results: The findings show that: The headmaster of SMPN 17 Kendari had a significant role in carrying out this program; Many readers (Sang Pembaca) were fond of fiction books, newspaper, and magazines; Additional facility such as comfortable place to read was a significant factor in implementing this program. Conclusion: It can be concluded that 40 Minutes with Parents/Guardians (Sang Penjemput) program, which was carried out with reading activity while picking up their children, is quite effective in influencing reading habits of the Parents/Guardians (Sang Penjemput). Through this program, it can also affect students’ reading literacy, as well as persuading nearby residents who live near SMPN 17 Kendari to read. Keywords: Creating Literacy Culture; Reading Interest; Sang Penjemput; SMP N 17 Kendari; 40 Minutes with “Sang Penjemput” Program